Multidisciplinary approaches to code switching - Isurin, Ludmila; Winford, Donald; De Bot, Kees (Studies in bilingualism, 2009)
The volume presents a selection of contributions by leading scholars in the field of code-switching. In the past the phenomenon of code-switching was studied within different subfields of linguistics and they all took their own perspectives on code-switching without taking into account findings from other subdisciplines. This book raises a question of a much broader multidisciplinary approach to studying the phenomenon of code-switching; calls for integration of disciplines; and illustrates how frameworks from one subfield can be applied to models in another. The volume includes survey chapter.